Image segmentation methods and edge detection: An application to knee joint articular cartilage edge detection - Mahmood , Nadeem; Shah, Asadullah; Waqas, Ahmad; Abubakar, Adamu; Kamran, Shafia; Zaidi, Syed Baqar (Little Lion Scientific Islamabad Pakistan, 2015)
Image segmentation is the process of partitioning a digital image into multiple segments and regions for further processing. Edge detection methods are widely used in the area of image processing for feature detection and extraction. In this paper we use human’s Knee MRI (Magnetic resonance imaging) images of patients and applied various image segmentation and edge detection methods for knee cartilage visualization. Also this paper focuses on providing an overview of important concepts, methods and algorithms commonly used for image segmentation and edge detection with focus on knee joint articular cartilage image segmentation and visualization